Towards a Syrianized health system in post-conflict Syria: challenges and recommendations - Orwa Al-Abdulla (Discover Health Systems)
Abstract The health system recovery in post-conflict Syria demands a contextualized and inclusive approach and represents a golden opportunity to build the system back better and foster social cohesion by addressing potential challenges such as governance and leadership, coordination, planning, and resource management. The article outlines key policy messages for stakeholders, emphasizing the importance of national ownership and equity in rebuilding the health system. The Ministry of Health must develop a recovery framework and prioritize policymaking, especially coordination, partnership, information management, planning, and sustainability. Evidence-based decision-making is key to addressing inequities, improving the health workforce, and avoiding inefficient resource management. Syrian humanitarian organizations are at a historic crossroads in supporting the health system recovery and transitioning from emergency response to long-term health system strengthening by adopting a Syrianized approach and collaborating with the Ministry of Health, donors, and other stakeholders. By emphasizing Syrianization, the article aims to provide an intellectual platform for health sector stakeholders to address these challenges at institutional and regional levels.